Development Of Pacu Jawi As A Leading Tourism Attraction In Tanah Datar - Arief Irvan; Maihasni Maihasni; Azwar Azwar (LPPM Universitas PGRI Sumatera Barat, 2022)
This study aims to identify and describe the efforts made by the Tanah Datar Tourism Office andthe impact of the efforts to develop the pacu jawi attraction. This study was analyzed usingstructural functionalism by Robert King Merton. This study uses a qualitative approach withdescriptive research type. The selection of informants was carried out by purposive sampling with atotal of 14 informants. Data was collected by means of active participation observation, in-depthinterviews and document studies. The results of the research were eleven attempts or efforts madeby the Tourism Office in the development of Pacu Jawi tourism attractions. The existence of theseeleven efforts has a real impact on the Region community and outside the Region community. Thereal impact is attracting tourist visits, buying and selling transactions at the location, generatingbusiness and services as well as opening up new jobs, preserving culture and maintaining unity andcohesiveness in the community. Apart from that, it also has a hidden impact from the developmentof Pacu Jawi tourist attractions, including improving and building region infrastructure, exploringthe potential of the region to be developed, paying attention to the Livestock Service andAgriculture Service to pay attention to breeding livestock and promoting agricultural welfare, aswell as revitalizing Minangkabau traditional arts.